ANALISIS SIFAT FISIKOKIMIA DAN ORGANOLEPTIK SAMBAL â€œCAHEROâ€ - Jordy W. Supit; Tineke M. Langi; Maya M. Ludong (COCOS, 2015)
ABSTRACT Â  Food diversification has important role in daily life. It could be as food tenacity, or to make some usual product have more function. Sauce is a product from fruits and have been known from long time ago. There are so many kind of sauce, such as chili sauce. Chili sauce is made from chili and it could be made with or without other ingredients. Combining Red chili and Red ginger, we can get a product with more function for health, because they both have bioactive substance such as antioxidant, and it could make the product spicier. Adding roa fish to make special taste from North Celebes. We can call this product â€œcaheroâ€ Sauce, abbreviated from â€œcabai Jahe roaâ€. The aim of this researched was to find which combination is the best based on organoleptic and physic and chemical characteristic. The result of this researched was combining red ginger with red chili to make sauce, gave a significant differentiation to the products. The organoleptic, physic and chemical characteristic showed that the best product was sauce contain 90% red chili and 10% with viscosity 766cP, Vitamin C 9,6mg.